2022
DOI: 10.1007/s40262-022-01194-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modelling to Identify Physiological and Drug Parameters Driving Pharmacokinetics in Obese Individuals

Abstract: Background Obese individuals are often underrepresented in clinical trials, leading to a lack of dosing guidance. Objective This study aimed to investigate which physiological parameters and drug properties determine drug disposition changes in obese using our physiologically based pharmacokinetic (PBPK) framework, informed with obese population characteristics. Methods Simulations were performed for ten drugs with clinical data in obese (i.e., midazolam, triazolam, caffeine, chlorzoxazone, acetaminophen, lora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Like CYP2E1, UGTs have shown a higher expression in people with obesity in some studies. Physiologically based pharmacokinetic modeling (PBPK) analysis of lorazepam indicated an 18% increase in UGT expression, with the increased enzyme expression in people with obesity confirmed using several other substrates 45 . Explanations for the increase in the activity of UGT include increased liver organ size and UGT expression in adipose tissue 38,46 .…”
Section: Decision Tree Framework To Inform On Drugs That Are Expected...mentioning
confidence: 99%
See 1 more Smart Citation
“…Like CYP2E1, UGTs have shown a higher expression in people with obesity in some studies. Physiologically based pharmacokinetic modeling (PBPK) analysis of lorazepam indicated an 18% increase in UGT expression, with the increased enzyme expression in people with obesity confirmed using several other substrates 45 . Explanations for the increase in the activity of UGT include increased liver organ size and UGT expression in adipose tissue 38,46 .…”
Section: Decision Tree Framework To Inform On Drugs That Are Expected...mentioning
confidence: 99%
“…Physiologically based pharmacokinetic modeling (PBPK) analysis of lorazepam indicated an 18% increase in UGT expression, with the increased enzyme expression in people with obesity confirmed using several other substrates. 45 Explanations for the increase in the activity of UGT include increased liver organ size and UGT expression in adipose tissue. 38,46 In a population pharmacokinetic analysis of garenoxacin, a primary UGT substrate, results showed that an obesity factor was a significant covariate on clearance (12.5% increase for the typical subject), leading to a significant increase in the clearance of patients who are obese when compared with patients of healthy weight.…”
Section: What Is the Role Of The Therapeutic Window Of A Drug For Inf...mentioning
confidence: 99%
“…47 Excessive fat deposition and chronic inflammation in the liver induced by obesity have reportedly caused a range of liver abnormalities. Specifically, hepatic blood flow was found to be increased in subjects with obesity as a result of increased cardiac output, 51,52 potentially leading to elevated hepatic elimination of drugs with a high extraction ratio (eg, propofol and fentanyl) following intravenous administration. 25,53,54 In addition, drugs characterized as obtaining a low to medium extraction ratio in subjects without obesity may shift to the category of a medium to high extraction ratio in the obese population due to the complex influence of obesity on hepatic blood flow, plasma protein binding, and intrinsic drug clearance.…”
Section: S67mentioning
confidence: 99%
“…For example, in the OSA drug development case mentioned above, PBPK models have been used for informing the effects of investigational drugs on gastric emptying time and the subsequent drug-drug interaction potential with orally administered concomitant medications in patients with OSA with obesity (BMI, 30 kg/m 2 or greater). 92,93 The second example is the integrated glucose-insulin (IGI) model, which is a mechanistic QSP model that quantifies the relationship between drug concentration, insulin lispro-aabc (Lyumiev), and postprandial glucose (PPG) response following administration of the insulin product. 94,95 The model describes the glucose absorption (intestinal transit through the stomach, duodenum, jejunum, and ileum), distribution, and elimination process in the body, which is regulated by a feedback relationship between insulin and glucose response.…”
Section: Providing Evidence For Seeking New Indicationsmentioning
confidence: 99%
See 1 more Smart Citation